Eye-Tracking Assistive Technology for Hands-Free Computer Navigation. (September 2021) - McCurley, Amelia; Nathan-Roberts, Dan
Eye-tracking technologies for computer navigation assist those with mobility and verbal impairments in interacting with the world around them. Studies found that these technologies have a profound positive impact on the lives of these individuals and those who care for them. This proceeding explores the popular features of eye-tracking systems and the challenges they present. Specifically, this proceeding evaluates camera configurations, camera types, and command selections through the lenses of cost, ease of use, and comfort. Current and future design guidelines based on these criteria are recommended to best aid individuals with these impairments.